Evaluasi Ketersediaan Obat di Puskesmas Wilayah Kota Banjarmasin Tahun 2024 - Fatmalika, Tria; Yuwindry, Iwan; Mukti, Yusuf Anggoro; Atmaja, Dewi Susanti (SENTRI: Jurnal Riset Ilmiah, 2025)
A common issue that often occurs in community health centers (puskesmas) is the mismatch in drug availability, where there is either an oversupply or a shortage, and expired or damaged medicines are still found in storage. This problem stems from poor drug management systems within the facilities. This study aimed to assess the availability of medicines in public health centers across the Banjarmasin City area in 2024. A quantitative approach with a cross-sectional design was used, involving six puskesmas selected through total sampling. Data was collected over one month, from May to June 2025, and analyzed descriptively to determine the percentage match between drug requests and actual receipts. The findings showed that the average match between requested and received drugs was 98.1%. However, in terms of availability, 60.8% of the drugs were categorized as out of stock, 7.2% as insufficient, 17.3% as sufficient, and 14.7% as oversupplied. These results indicate that despite a high match rate between requested and received drugs, the overall availability of medicines in Banjarmasin Timur puskesmas is inadequate, with most categorized as out of stock.